Empty container reposition using max-min review system: Simulation approach. Issue 1 (February 2021) - Budipriyanto, A; Novianti, M D; Susanto, T
Abstract: Global economic conditions and differences in the ability and economic competitiveness of each country cause an imbalance between exports and imports. Shipping of goods is carried out mostly by sea transportation through the use of containers and involves the port as the exit and entry of goods. An imbalance in export-import causes the number of containers in some ports to have a surplus, while others have a deficit. To maintain container availability, shippinglines must adjust the balance by repositioning from a surplus port to a deficit port. Shippinglines must determine the inventory to meet the needs at the port and the number of containers that can be repositioned to the other ports that need it. If the inventory at the port reaches a minimum level, then the order must be immediately carried out, on the contrary, it will be repositioned to another port that needs it. By adopting the concept of a review system (U, D), when the inventory is less than U, an order of Q is immediately placed. But if the inventory is greater or equal to D, repositioning is carried out. Repositioning is done by I-D. In this study, the maximum inventory value is determined based on the value of the inventory service level of 95%. From the simulation results it was concluded that the min-max review system policy with a service level of 95% could reduce inventory by 35.64% and reduce shortage by 8.82%.